Fetal Pulmonary Response After Fetoscopic Tracheal Occlusion for Severe Isolated Congenital Diaphragmatic Hernia - Ruano, Rodrigo; da Silva, Marcos Marques; Duarte Bonini Campos, Juliana Alvares; Papanna, Ramesha; Moise, Kenneth; Tannuri, Uenis; Zugaib, Marcelo (Lippincott Williams & Wilkins, 2012)
OBJECTIVE: To estimate the response in lung growth and vascularity after fetal endoscopic tracheal occlusion for severe congenital diaphragmatic hernia in the prediction of neonatal survival.METHODS: Between January 2006 and December 2010, fetal lung parameters (observed-to-expected lung-to-head ratio; observed-to-expected lung volume; and contralateral lung vascularization index) were evaluated before fetal tracheal occlusion and were evaluated longitudinally every 2 weeks in 72 fetuses with severe isolated congenital diaphragmatic hernia. Thirty-five fetuses underwent fetal endoscopic tracheal occlusion and 37 cases did not.RESULTS: Survival rate was significantly higher in the fetal endoscopic tracheal occlusion group (54.3%) than in the no fetal endoscopic tracheal occlusion group (5.4%, P<.01). Fetal endoscopic tracheal occlusion resulted in a significant improvement in fetal lung size and pulmonary vascularity when compared with fetuses that did not go to the fetal intervention (increase of the observed-to-expected lung-to-head ratio, observed-to-expected total lung volume, and contralateral pulmonary vascularization index 56.2% compared with 0.3%, 37.9% compared with 0.1%, and 98.6% compared with 0.0%, respectively; P<.01). Receiver operating characteristic curves indicated that the observed-to-expected total fetal lung volume was the single best predictor of neonatal survival before fetal endoscopic tracheal occlusion (cutoff 0.23, area under the curve [AUC] 0.88, relative risk 5.3, 95% confidence interval [CI] 1.4-19.7). However, the contralateral lung vascularization index at 4 weeks after fetal endoscopic tracheal occlusion was more accurate in the prediction of neonatal outcome (cutoff 24.0%, AUC 0.98, relative risk 9.9, 95% CI 1.5-66.9) with the combination of observed-to-expected lung volumes and contralateral lung vascularization index at 4 weeks being the best predictor of outcome (AUC 0.98, relative risk 16.6, 95% CI 2.5-112.3).CONCLUSION: Fetal endoscopic tracheal occlusion improves survival rate by increasing the lung size and pulmonary vascularity in fetuses with severe congenital diaphragmatic hernia. The pulmonary response after fetal endoscopic tracheal occlusion can be used to predict neonatal survival. (Obstet Gynecol 2012; 119: 93-101) DOI: 10.1097/AOG.0b013e31823d3aea